A study on a service performance of express bus companies in a competitive market - Hassan, Fauziah (1995)
Competition between the firms in each of the five modes of transportation does not only exist, but is of major importance particularly to the express bus operators. The existance of competition in transport industry, is felt and made aware by the operators. The express bus industry in Malaysia is undergoing a major transition where 1423 new licenses is being released by Commercial Vehicle Licensing Board (CVLB) on the 26th March 1992, The action of CVLB allowed competition between bus services after about 20 years of protection of established services through road services licensing. The Johor Bahru - Kuala Lumpur route was very much sought after by transport operators. This is due to the fact that it is one of the most profitable route in Peninsular Malaysia. This sudden overflow of services competing for the JB - KL route had caused highly competitive market situation among express bus companies. The intense competitive environment has affected both users and the bus operators. Generally, the impact on the operators is the intense competition which has brought forth the problems of surplus in services and smaller market share; and this is the subject of the study for which the Express Bus Costing Survey (EBCS) was conducted with detailed records of service and financial performance of four express bus companies operating the service on the JB-KL route. In the current transport environment, the express bus operators have to be competitive in order to survive and prosper. The express bus companies which are operating in the highly competitive market often have to deal with the problems to achieve profitability. Too many permits of the JB-KL route have produced a wasteful competition for local express bus services, thus leading to a stage where it becomes harmful to the industry. Due to the intense competition, recommendations of changing the structure of the bus industry are given in this study. The franchising bus system and public transport co-ordination have been suggested to be the best solutions to the problems.